2022
DOI: 10.3390/pharmaceutics14061116
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and Evaluation of Forcespun Gelatin Nanofibers as an Isorhamnetin Glycosides Delivery System

Abstract: Opuntia ficus-indica (L.) Mill (OFI) is considered a natural source of bioactive phytochemicals, mainly isorhamnetin glycosides (IRGs). These compounds have demonstrated antioxidant, anti-inflammatory, and anticancer activities, among others. The development of a suitable delivery system for these compounds is needed to improve their chemical and biological stability. This study aimed to evaluate the feasibility of fabrication and characterization of IRG-loaded gelatin (GL) forcespun fibers and crosslinking wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The structures of polyphenolic compounds contain several active catechol groups [notably, two hydroxyl groups (OH) immediately adjacent to the benzene ring], which can form covalent bonds with functional groups on nanocarriers or polymers through processes, such as esterification or etherification (García‐Valderrama et al, 2022; Pérez‐Silva et al, 2023). Additionally, the aromatic ring structure of these compounds offers spatial steric effects, enabling delayed or controlled release of drugs (Kong et al, 2018).…”
Section: Development Of Nanocarriers Based On Plant‐derived Active Co...mentioning
confidence: 99%
“…The structures of polyphenolic compounds contain several active catechol groups [notably, two hydroxyl groups (OH) immediately adjacent to the benzene ring], which can form covalent bonds with functional groups on nanocarriers or polymers through processes, such as esterification or etherification (García‐Valderrama et al, 2022; Pérez‐Silva et al, 2023). Additionally, the aromatic ring structure of these compounds offers spatial steric effects, enabling delayed or controlled release of drugs (Kong et al, 2018).…”
Section: Development Of Nanocarriers Based On Plant‐derived Active Co...mentioning
confidence: 99%
“…In the research, a novel bioinspired GL-based drug delivery system is demonstrated. It may be used to deliver controlled amounts of phytochemical medications for tissue regeneration and the treatment of wounds [ 156 ].…”
Section: Biomedical Application Of Rementioning
confidence: 99%
“…FS boasts high fiber fabrication rates and the ability to process a large range of materials such as polymers, carbon, ceramics, etc. FS compiled a lot of attention in recent years, in drug delivery and energy. For instance, polycaprolactone/mercaptophenyl methacrylate functionalized carbon nano-onions (PCL/f-CNOs) nanofibers were primed by using FS for controlled anticancer drug release. Doxorubicin (DOX) is well-known anticancer drug with the ability to kill cancer cells via the inhibition of RNA and DNA biosynthesis.…”
Section: Nanofiber Scaffolds For Biomedical Applicationsmentioning
confidence: 99%